Kolaborasi Antar Aktor Dalam Program Desa Bebas Api Di Desa Sungai Ara Kabupaten Pelalawan - Manurung, Pesta Rida; Dadang Mashur (Jurnal Ilmu Administrasi Negara (JUAN), 2021)
To help reduce the level of forest and land fires that continue to occur in Riau Province, Pelalawan Regency, PT Riau Andalan Pulp and Paper, one of the paper and pulp mills, initiated the Fire Free Village Program which has been running for five years, formed in 2015. In one of the villages that took part in the PT Riau Andalan Pulp and Paper program, one of them was Sungai Ara Village which was successful in agriculture. The Fire Free Village Program was developed with five programs, namely: Fire free village awards, sustainable agricultural assistance, involvement of the leader crew in fire prevention, assistance in clearing land without burning, monitoring air quality. This study aims to determine the process Collaboration. This research uses a qualitative approach with descriptive data. The results showed that first, the Collaboration Process between Actors in the Fire Free Village Program in Sungai Ara Village, Pelalawan Regency was running well according to face-to-face dialogue, mutual understanding, building trust, commitment to the process and temporary impacts. Second, the supporting factors for collaboration are the budget, the availability of facilities and infrastructure, communication and community participation.